2004
DOI: 10.1029/2003jd004271
|View full text |Cite
|
Sign up to set email alerts
|

Aerial measurement of air pollutants and aerosols during 20–22 March 2001 over the East China Sea

Abstract: [1] Aerial measurement of atmospheric pollutants was carried out over the East China Sea on 20, 21, and 22 March 2001. High concentrations of not only gaseous species (maximum concentrations of SO 2 > 10 ppb and O 3 > 100 ppb in the marine boundary layer) but also particulate matter (PM) (average concentration of PM 2.5 $ 30 mg m À3 and PM 10 $ 1000 mg m À3 in the marine boundary layer) were observed on 21March. Such high concentrations were observed only at low altitude. A cold front passing over the Korean P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 24 publications
6
32
0
Order By: Relevance
“…Both the global and regional aspects of the long-range transport of pollutants are very important, and several cooperative international experiments have thus been conducted in the western Pacific region (Huebert et al, 2003;Parrish et al, 2004;Nakajima et al, 2007). The current authors have also reported the results of aerial observations of atmospheric pollutants in a source region in China (Hatakeyama et al, 2005;Wang et al, 2006;Wang et al, 2007;Wang et al, 2008), and a receptor region (Hatakeyama et al, 1995a, b;Hatakeyama et al, 1997;Hatakeyama et al, 2004). Transformation of pollutants during their long-range transport is an important problem from the perspective of regional air quality and acid rain.…”
Section: Anthropogenic Emissions Have Been Increasing In Eastmentioning
confidence: 85%
See 1 more Smart Citation
“…Both the global and regional aspects of the long-range transport of pollutants are very important, and several cooperative international experiments have thus been conducted in the western Pacific region (Huebert et al, 2003;Parrish et al, 2004;Nakajima et al, 2007). The current authors have also reported the results of aerial observations of atmospheric pollutants in a source region in China (Hatakeyama et al, 2005;Wang et al, 2006;Wang et al, 2007;Wang et al, 2008), and a receptor region (Hatakeyama et al, 1995a, b;Hatakeyama et al, 1997;Hatakeyama et al, 2004). Transformation of pollutants during their long-range transport is an important problem from the perspective of regional air quality and acid rain.…”
Section: Anthropogenic Emissions Have Been Increasing In Eastmentioning
confidence: 85%
“…NaCl + HNO 3  NaNO 3 + HCl 2NaCl + H 2 SO 4  Na 2 SO 4 + 2HCl Nitric acid is usually well neutralized with calcium compounds within the air mass transported long range over the East China Sea (Hatakeyama, 2004). Therefore, the contribution of sulfuric acid, which is formed by the oxidation of SO 2 during the transport, should become larger.…”
Section: Sulfate Formation and Chlorine Lossmentioning
confidence: 99%
“…[4] The sporadic Asian dust events might not be the only occasions when the dust modification can be studied, because dust-laden air is often dry and separated from polluted air as it sweeps across the region [Zhang et al, 2005;Hatakeyama et al, 2004;Bates et al, 2004;MaxwellMeier et al, 2004]. Laboratory studies suggest increased uptake coefficients of HNO 3 , NO 2 , and SO 2 gases on mineral dust under higher relative humidity (which determines the amount of water associated with the particles) [Dlugi et al, 1981;Goodman et al, 2000;Hanisch and Crowley, 2001;Underwood et al, 2001;Usher et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…Since we did not measure chemical compositions of aerosol particles, it is uncertain how much sea salt contributed to the sulfate concentration. According to the previous studies, sea-salt related sulfate in particulate matters usually occupied only a small fraction in total sulfate in this area when the air parcels were from the Asian continent (Hatakeyama et al, 2004;Koike et al, 2003).…”
Section: Mt Sakurajimamentioning
confidence: 71%
“…Sahu et al, 2009;Hatakeyama et al, 2004;Koike et al, 2003) and model simulations (e.g. Heald et al, 2006;Takemura et al, 2003;Uno et al, 2003).…”
Section: Introductionmentioning
confidence: 99%